Program Budgeting and Governance of the Budget at Local Level - Iliev, Ivaylo (Research Papers, 2018)
The governance of the budget on local level key instrument for the achievement of the pre-set goals of the municipalities. A well-organized budget helps to improve the living environment for the citizens. The compilation and implementation of the program budget at local level has its peculiarities. The program budget allows the creation of link between inputs and outputs and it should be able to evaluate the efficiency of implementation. The optimization of financial management at local level can be achieved through the use of various measures. The municipal administration plays an active role in the program budgeting process. Program budget management at local level is developing and it is necessary to take in account the new management trends.
Keywords: Local self-governance; Budgeting; Innovative approaches; Programs